PRICE FORECASTING OF STRATEGIC FOOD COMMODITIES IN VARIOUS MARKETS IN MALANG REGENCY: IMPLEMENTATION OF THE ARMA-GARCH MODEL - Sujarwo Sujarwo; Fitrotul Laili (Socio-Economics/Agribusiness Department, 2023)
Fluctuations in food prices can trigger vulnerability, disrupting people's access to food. This study aims to predict the prices of strategic food commodities: rice, corn, shallots, garlic, cayenne pepper, large chilies, chicken meat, chicken eggs, beef, cooking oil, and granulated sugar at the wholesaler level in the district. Poor. The research method used is the ARMA-GARCH forecasting method. Price forecasting carried out on all strategic food commodities in Malang Regency shows a fluctuating pattern with a tendency for price increases, with an average change increasing gradually in each period. The causality relationship in various markets about price changes in strategic food commodities in Malang Regency shows a unidirectional and two-way causality pattern.